CREATIVE ARTS IN SPECIAL EDUCATION: ENHANCING EXPRESSION, COMMUNICATION AND COGNITIVE DEVELOPMENT - Naresh Kumar Jaiswal (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Abstract With an emphasis on how artistic pursuits including visual arts, music, theatre, and dance can improve expression, communication, and cognitive development among kids with special needs, this study paper examines the tremendous impact of creative arts in special education. This paper demonstrates the beneficial effects that creative arts interventions can have on the lives of these kids by looking at theoretical frameworks, empirical investigations, and practical applications. According to a synthesis of studies, including creative arts in special education curricula not only promotes communication and self-expression skills but also encourages cognitive development, resulting in more comprehensive and inclusive educational experiences.